Identifying the Sensitivity of Complex Human-Water Systems Using a Qualitative Systems Approach - Höllermann, Britta; Evers, Mariele (Frontiers in Water, 2020)
As the complexity of human-water systems interactions is increasing, the need for an integrated view on water-related issues becomes more important. In this study we focus on the qualitative description of human-water interactions with the aim to identify sensitive system variables which may alter the established water resource system. Qualitative system analysis based on extensive expert elicitation regarding reservoir management was applied to disclose the politics behind water management visions and measures and to identify sensitive system variables where the different perspectives of stakeholders and decision-makers enter the human-water system in response to environmental change and societal processes. This highlights the interplay of the distribution of water and the distribution of power which is central within human-water systems. The results are two-fold. First, we show, that such a qualitative approach is helpful in revealing sensitive system variables. Second, our analysis identifies i) perception of change, ii) risk to users, and iii) discrepancy of actual and desired level of reservoir as the sensitive system variables deciding about thresholds in the specific setting of our case study. Hereby, the case study highlights also the applicability and usability of our approach. Aiming at sustainable water management, knowledge about the sensitive system variables is crucial to understand the effects of different visions and, hence, action within the human-water system to cover the whole range of societal responses. While we applied this approach on a reservoir management example, we are confident that this approach is transferable to other water management cases for identifying the complexity of interactions, sensitive system variables, and critical variables of change and transformation.